Watch and Wait Management of Inactive Cystic Echinococcosis - Does the Path to Inactivity Matter - Analysis of a Prospective Patient Cohort. - Marija Stojkovic; Kerstin Daniela Rosenberger; Franziska Steudle; Thomas Junghanss (Public Library of Science (PLoS), 2016)
Overdiagnosis and overtreatment are rarely discussed in the context of NTDs despite their relevance for patients under the care of health services with limited resources where the risks of therapy induced complications are often disproportionate to the benefit. The advantages of cyst staging-based management of patients with cystic echinococcosis (CE) are not yet fully explored. Questions are: Do inactive cysts (CE 4 and CE 5) need treatment and is there a difference between cysts which reach CE4 and CE5 naturally or by benzimidazole therapy?Analysis of long-term follow-up data from a prospective CE patient cohort of 223 patients of a national clinical center for echinococcosis. The event of interest "relapse" was defined as the reversal of a cyst from an inactive stage (CE4, CE5) back to an active stage. The watch &wait (ww) group included 30 patients with 46 inactive cysts who never received medical treatment. The benzimidazole-treated (med) group included 15 patients with 17 cysts. There was no relapse in the ww-group whereas 8/17 cysts showed relapse within 18 months after treatment in the med-group. Loss to follow-up was 15.5%.Data from the watch & wait group impressively show how stable naturally inactivated cysts are in contrast to cysts which reach inactivity through treatment with benzimidazoles. A substantial proportion of patients can be spared from treatment through cyst staging. Cysts which inactivated through a natural course do not relapse with very high likelihood. We recommend follow up of 5 years to confirm the stability of the inactive stage. Cysts driven into inactivity through benzimidazole therapy instead need careful monitoring to identify those which reactivate (around 50% within 18 months). 5 years follow-up appears safe to make a final decision on the need for further monitoring.